Financial Integration and Economic Growth: Empirical Evidence from the Republic of Georgia - Phutkaradze, Zaur; Tsintsadze, Asie; Phutkaradze, Beka (European Journal of Sustainable Development, 2019)
Despite the vast amount of research studies, there is no clear and unambiguous opinion among economists on how the international financial integration (IFI) affects economic growth. This paper attempts to investigate the relationship between financial integration and economic growth in the Republic of Georgia. The study employs a log-linear equation for economic growth and covers the time-series data over the period of 1995–2016. OLS estimations do not provide statistically significant evidence for IFI-growth relationship. However, although the significance of this linkage is not apparent, it is important to highlight the main tendency – financial integration plays a positive role when the country has a relatively stable currency and negative role during the period of significant currency fluctuations. Outcomes of the study are consistent with our theory and support prior researches in this area. Keywords: Financial integration; economic growth; empirical model